Relationship between Knowledge, Attitude and Anxiety with the Implementation of Health Protocols among Food Vendors at the UMS Campus Environment - Nur Fauzia Asmi; Kiki Puspasari (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Food vendors are a group that is prone to contracting Covid-19 because they are still selling foods during a pandemic which can be a source of contamination through droplets or touching surfaces affected by droplets. Food vendors who do not implement health protocols are very vulnerable to being infected with Covid-19 which can further infect other people. This study aims to determine the relationship between knowledge, attitude and anxiety with the implementation of health protocols among food vendors at the UMS campus environment. This was an analytical observational study with a cross sectional approach. The current study was conducted at the Suherman Medical University (UMS) campus Environment, Pasir Gombong area, Bekasi District, from September to November 2021. The population in this study involved food vendors in the Pasir Gombong area with a sample size calculated using the Lemeshow formula which obtained 64 food vendors. The samples were selected using accidental sampling technique. Data collection was conducted by enumerators through interviews using questionnaires and observations. Data were analyzed using Chi-Square test, fisher's exact and logistic regression to determine the relationship between each variable. Furthermore, multivariate analysis was applied using the logistic regression test. The results of the study showed that there was a significant relationship between anxiety and implementation of health protocols with a p-value of 0.024 and OR=11.7 (1.214–113.3), between knowledge and implementation of health protocols with a p-value of 0.001 and OR= 6.3 (1.937–20.880); between attitude and implementation of health protocol with a p-value  of 0.000 and OR=8.6 (2.579-29.126). It can be concluded that knowledge, attitude and anxiety had a significant relationship with the implementation of health protocols among food vendors. Continuous education can be an effort to prevent health problems.